Multi-access edge computing offloading in maritime monitoring sensor networks - Xin SU; Ziyi WANG; Yupeng WANG; Siyuan ZHOU (物联网学报)
Multi-access edge computing can effectively guarantee the low-latency, high-reliability data transmission of ocean monitoring sensor networks and various related maritime applications.In the offshore scenario, two offloading models of multi-user single-hop unicast and multi-user multi-hop unicast were established in combination with the distribution of edge computing resources.The mixed integer nonlinear programming was used to separate optimization targets and effectively allocate transmission power.The unloading decisions were made by improving the traditional artificial fish swarms algorithm.The results show that the proposed optimization algorithm can reduce the network delay by nearly 19% compared with the traditional scheme.In the far-sea scenario, a multi-user single-hop unicast offloading model was established, and a reasonable channel allocation algorithm was proposed based on the network connection probability.The results show that when the network connection time is sufficient, the number of allowable sub-channels can be increased to reduce the network delay.When the network connection time is limited, the number of unloaded marine user equipment can be controlled to ensure the network transmission delay.